2021
DOI: 10.1155/2021/6761364
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Pulse Coupled Neural Network Algorithm in the Diagnosis and Treatment of Severe Sepsis Complicated with Acute Kidney Injury under Ultrasound Image

Abstract: The objective of this study was to explore the diagnosis of severe sepsis complicated with acute kidney injury (AKI) by ultrasonic image information based on the artificial intelligence pulse coupled neural network (PCNN) algorithm. In this study, an algorithm of ultrasonic image information enhancement based on the artificial intelligence PCNN was constructed and compared with the histogram equalization algorithm and linear transformation algorithm. After that, it was applied to the ultrasonic image diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Studies showed that ultrasound diagnosis technology has high accuracy as an auxiliary method for the diagnosis of kidney diseases. Determination of the renal blood flow resistance index (RI) can reflect renal tubular necrosis in patients, which has a clinical application value for AKI diagnosis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that ultrasound diagnosis technology has high accuracy as an auxiliary method for the diagnosis of kidney diseases. Determination of the renal blood flow resistance index (RI) can reflect renal tubular necrosis in patients, which has a clinical application value for AKI diagnosis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The cluster analysis of high-frequency keywords and references can identify the hot spots and frontiers of machine learningrelated AKI research, among which "prognosis", "sepsis", "critically patients", "MIMIC", and "XGBoost" are the hot spots of research based on the time overlay map. The current research on machine learning in sepsis-related AKI mainly includes two aspects: one is the study of constructing predictive models (37), and the other is the auxiliary addition to the analysis and processing of ultrasound images of AKI (8,38). In several studies, the diagnosis and treatment effect of sepsis-related AKI has been greatly improved by introducing XGBoost, deep learning and neural network algorithms (8,37,38), but its effectiveness in clinical practice remains to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The current research on machine learning in sepsis-related AKI mainly includes two aspects: one is the study of constructing predictive models (37), and the other is the auxiliary addition to the analysis and processing of ultrasound images of AKI (8,38). In several studies, the diagnosis and treatment effect of sepsis-related AKI has been greatly improved by introducing XGBoost, deep learning and neural network algorithms (8,37,38), but its effectiveness in clinical practice remains to be confirmed. HA-AKI in critically ill patients has always been one of the research hotspots in this field (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Ying et al [ 250 ] proposed a PCNN method for the diagnosis of severe sepsis complicated by AKI using an ultrasonic image. Their study explains their CNN-based ultrasonic image enhancement technique, which was later compared with the histogram equalization and linear transformation algorithms.…”
Section: Discussionmentioning
confidence: 99%